Effects of comorbidity, substance type and personality disorders on duration among inpatients with alcohol and substance use disorder - Çıray, Remzi Oğulcan; Kurt, Ümmü Seda; Evren Kılıçaslan, Esin (Journal of Dependence, 2018)
Objective: The aim of this study is to investigate whether there is a relationship between the length of hospital stay and the types of substance used, personality disorders and comorbidity among inpatients with alcohol and substance use disorder.Method: A total of 131 patients who were diagnosed as alcohol-substance use disorder according to DSM-5 criteria were included in the study. The sociodemographic data form was given to the volunteers and comorbid psychiatric disorders were determined. The number of days on which the patients completed the treatment and the types of substances they used were noted.Results: A statistically significant relationship was found between the duration of hospital stay and age and the substances used. This significance was found to be especially between alcohol group and opioid group.Conclusion: The relationship between the type of substance used and the length of hospital stay may be related to the withdrawal symptoms of the substances and the sociodemographic status of the substancedependent individuals. A positive correlation between age and length of hospital stay can be interpreted as increasing compliance with age.
Keywords: addiction; hospital stay; comorbidity; substance use; personality disorders